Preparation of active packaging with antioxidant and antimicrobial activity based on astaxanthin and chitosan - Sanches-Silva, A. (2011)
The project ‘Preparation of active packaging with antioxidant and antimicrobial activity based on astaxanthin and chitosan’ (PAPAAABAC, in Spanish PEACAABAQ) brings together a multi-disciplinary team from Mexico, Spain and Portugal, with expertise in different areas of food and polymer sciences. The working programme includes optimisation of the extraction and characterisation of astaxanthin and chitosan from shrimp waste, and incorporation of these compounds into plastic (polymeric matrices), in order to obtain new packaging with antioxidant and antimicrobial properties (active packaging) and finally control-release studies which are carried out in order to determine the quantity of active compounds that should be included in the packaging. This is a 2-year project which started in 2009 and is funded by FONCYCIT (Fund for International Cooperation of Science and Technology EU-Mexico; Fondo de Cooperación Internacional de Ciencia y Tecnologia Unión Europea-Mexico) under the coordination of Professor Jaime López Cervantes from the Technological Institute of Sonora (ITSON).